Mitochondria: new players in homeostatic regulation of firing rate set points. Issue 8 (August 2021) - Ruggiero, Antonella; Katsenelson, Maxim; Slutsky, Inna
Abstract : Neural circuit functions are stabilized by homeostatic processes at long timescales in response to changes in behavioral states, experience, and learning. However, it remains unclear which specific physiological variables are being stabilized and which cellular or neural network components compose the homeostatic machinery. At this point, most evidence suggests that the distribution of firing rates among neurons in a neuronal circuit is the key variable that is maintained around a set-point value in a process called 'firing rate homeostasis.' Here, we review recent findings that implicate mitochondria as central players in mediating firing rate homeostasis. While mitochondria are known to regulate neuronal variables such as synaptic vesicle release or intracellular calcium concentration, the mitochondrial signaling pathways that are essential for firing rate homeostasis remain largely unknown. We used basic concepts of control theory to build a framework for classifying possible components of the homeostatic machinery that stabilizes firing rate, and we particularly emphasize the potential role of sleep and wakefulness in this homeostatic process. This framework may facilitate the identification of new homeostatic pathways whose malfunctions drive instability of neural circuits in distinct brain disorders. Highlights: Firing rate distributions and mean firing rate (MFR) present homeostatically regulated variables in central neural circuits. Mitochondrial Ca 2+ buffering is involved in the regulation of the main homeostatic modules underlying firing rate stabilization: set points, sensors, and effectors. The core homeostatic machinery can be identified by a dual-challenge approach. Using this framework, the mitochondrial dihydroorotate dehydrogenase (DHODH) enzyme has been uncovered as a regulator of MFR set points in hippocampal networks. MFRs and firing rate distributions are homeostatically regulated by sleep in specific neural circuits. As products of DHODH enzymatic activity are inhibited by sleep, DHODH inhibition may mediate a homeostatic decrease of MFRs during sleep. Mitochondrial dysfunctions constitute a common hallmark of distinct brain disorders due to a central role of mitochondria in homeostatic firing rate regulation.